2017
DOI: 10.1159/000455282
|View full text |Cite
|
Sign up to set email alerts
|

Macular Edema of Choroidal Origin

Abstract: Macular edema is most often clinically defined as an accumulation of serous fluid within the neurosensory retina with increased thickness of the central retina. In exudative age-related macular degeneration the leakage of fluid from the choroidal new vessels may be the origin of macular edema. Their abnormal permeability and the inflammatory reaction are mechanisms involved in this accumulation of fluid, which occurs in all layers. Cystoid macular edema is more often associated with subepithelial occult choroi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…ME is clinically defined as an accumulation of serous fluid within the neurosensory retina, with increased thickness of the central retina. Some researches have shown that the leakage from the choroidal new vessels, predominantly VEGF-induced, may produce a large accumulation of fluid under the neurosensory retina [ 15 ]. Anti-VEGF has now become the cutting-edge treatment choice for ME, due to its excellent visual and anatomic improvement [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…ME is clinically defined as an accumulation of serous fluid within the neurosensory retina, with increased thickness of the central retina. Some researches have shown that the leakage from the choroidal new vessels, predominantly VEGF-induced, may produce a large accumulation of fluid under the neurosensory retina [ 15 ]. Anti-VEGF has now become the cutting-edge treatment choice for ME, due to its excellent visual and anatomic improvement [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the choroid sits outside the site of the outer BRB, together with Bruch’s membrane, it may still influence fluid homeostasis across the barrier. For instance, the hydraulic conductivity of Bruch’s membrane decreases with age ( 80 ), which is a possible factor in the accumulation of subretinal fluid in exudative age-related macular degeneration ( 81 ). Changes to the choroid are also likely to affect processes of retinal fluid absorption across the RPE cells.…”
Section: Mechanisms Of Macular Edemamentioning
confidence: 99%